Consumo Per Capita e perdas no Sistema de Distribuição de Água no Município de Boa Vista/RR - Caldas, Karolyne Paulino Freire de (2023)
The present research deals with the investigation of per capita consumption and the index of losses in the distribution for the capital Boa Vista of the State of Roraima. Due to the New Sanitation Regulatory Framework, set forth in Law 14.026/2020, the need to formulate strategies to enable access to universal sanitation has become a matter of great prominence today. That way, this study search to contribute in a technical way to the elaboration of a methodology that makes it possible to study and determine the current situation of the city of Boa Vista in relation to the per capita consumption pattern, remaining this differential result by neighborhoods and zones, arranged in the maps in appendix. In addition, the inheritance of the loss rates using the methodology of the Instituto Trata Brasil, considered more current values regarding the supply and distribution of water in the capital, through data provided by Companhia De Água E Esgotos De Roraima - CAER. The relationship between losses in water distribution and consumption per capita in a network water can be complex and influenced by several facts, by the results obtained it was possible to observe whether there was a direct relationship between the two social aspects presents in the Boa Vista distribution system. The methodology used for sensing the loss rates was data analysis based on the analysis method of the National Sanitation Information System – SNIS, using data provided by the Company. Through the Excel program, it was possible to determine the most relevant statistics for analyzing the current situation of the capital. With the distribution loss index at 56.04%, and the revenue loss index at 62.75% for the year 2021. As for per capita consumption, a specific methodology was used based on the random choice of 05 (five) families in the neighborhoods contained in the capital, in order to determine per capita consumption with more realistic data. The value found for the municipality of Boa Vista was 198.46 L/hab.day in the year 2020. The results of this work identified the problems that intensify these losses, understanding their causes and conditions and the preventive measures applied to this situation. Thus, with an adequate plan of action, it is possible to obtain several benefits such as savings in electricity, labor, and finally the redirection of investments to meet the growth in population demand.